Security in virtual worlds, 3D webs, and immersive environments models for development, interaction and management - Rea, Alan (Information Science Reference, 2011)
"This publication discusses the uses and potential of virtual technologies and examines secure policy formation and practices that can be applied specifically to each"--Provided by publisher